Pengaruh pelaksanaan program gerakan literasi sekolah dan minat baca terhadap keterampilan menulis narasi siswa kelas IV sekolah dasar - Dewi, Nadia Grapilia Permata; Chumdari, Chumdari; Suharno, Suharno (Universitas Sebelas Maret, 2022)
This study aims to 1) knowing the effect of the implementation school literacy program on the narrative writing skills of fourth-grade elementary school students; 2) knowing the effect of the reading interest on the narrative writing skills of fourth-grade elementary school students; 3) knowing the effect of the implementation school literacy program and the reading interest together on the narrative writing skills of fourth-grade elementary school students. This is quantitative research using a correlational method. The population in this study is all fourth-grade students of state elementary schools in the sub-district of Boyolali in the academic year 2021/2022. The research sample is fourth-grade students from three elementary schools who had been selected using the cluster random sampling technique. The results of data analysis, it can be concluded that 1) there is a positive and significant influence from the implementation of the school literacy movement program on student narrative writing skills by 45.1%; 2) there is a positive and significant influence of reading interest in student narrative writing skills by 2 2.6%; 3) there is a positive and significant influence from the implementation of the school literacy program and interest in reading together on students' narrative writing skills by 67,7%.